Effect of Sensitive pH on Hydroxyapatite Properties Synthesized from Chicken Eggshell - Ferli Septi Irwansyah; Azhari Yusuf; Diana Rakhmawaty Eddy; Risdiana Risdiana; Atiek Rostika Noviyanti (Universitas Gadjah Mada, 2022)
The hydrothermal method has effectively synthesized hydroxyapatite (HA). This study aimed to analyze the effect of pH on the properties (purity, crystallinity, and size) of HA crystals. HA synthesis of chicken eggshells was carried out using the hydrothermal method at temperatures of 230 °C with pH 9 and 9.34. The characteristics of HA are determined by XRF, XRD, FTIR, and TEM. The composition of the most significant compound obtained from the results of XRF analysis is CaO (97.5%). The XRD analysis showed that the purity of HA with pH 9.00 and 9.34 obtained was 97.8 and 96.6%, with the crystallinity of 56.46 and 56.96%. It was also obtained that the size of crystal HA was 21.8 and 15.7 nm for samples synthesized at pH 9.00 and 9.34. The results showed that the purity and size of HA were affected by differences in the pH synthesis and were relatively the same for its crystallinity which directly affects the value lattice parameter. The properties of HA produced by the hydrothermal method have met the criteria for biomedical applications.